2020
DOI: 10.34172/jhp.2020.21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sulfur and foliar application of Zn and Fe on yield and biochemical factors of cumin (Cuminum cyminum L.) under irrigation regimes

Abstract: Introduction: Cumin, due to its food and medicinal properties, is one of the important plant species in the world. Moreover, water and nutrition deficiencies are serious abiotic stress factors. So, this experiment was conducted with the aim of investigating the effects of sulfur and foliar application of Fe and Zn on yield and biochemical characteristics of cumin under irrigation regimes. Methods: The experiment was conducted as a split plot on the basis of a completely randomized block design during the 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Numerous studies have emphasized the importance of using micronutrients as foliar sprays and their positive impact on stimulating and strengthening the development and output of medicinal and aromatic plant species. Several studies have been demonstrated how zinc applied topically might affect vegetative development and lessen the negative consequences of shortages of water on various plant species, on various plant species, such as moringa plan [47]t;lemon grass [48], and cumin [49].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have emphasized the importance of using micronutrients as foliar sprays and their positive impact on stimulating and strengthening the development and output of medicinal and aromatic plant species. Several studies have been demonstrated how zinc applied topically might affect vegetative development and lessen the negative consequences of shortages of water on various plant species, on various plant species, such as moringa plan [47]t;lemon grass [48], and cumin [49].…”
Section: Discussionmentioning
confidence: 99%